Pledgeability and Asset Prices: Evidence from the Chinese Corporate Bond Markets - CHEN, HUI; CHEN, ZHUO; HE, ZHIGUO; LIU, JINYU; XIE, RENGMING (Journal of Finance, 2023)
ABSTRACT We provide causal evidence on the value of asset pledgeability by exploiting a unique feature of Chinese corporate bond markets: bonds with identical fundamentals are traded on two segmented markets with different rules for repo transactions. Using a policy shock that rendered AA+ and AA bonds ineligible for repo on one market only, we compare how bond prices changed across markets and rating classes around this event. When the haircut increases from 0% to 100%, bond yields increase by 39 bps to 85 bps. These estimates help us infer the magnitude of the shadow cost of capital in China.